Meningkatkan Hasil Belajar Siswa Pada Materi Ikatan Kimia Dengan Menggunakan Model Pembelajaran Kooperatif Tipe STAD Pada Siswa Kelas X3 SMA Negeri 3 Gorontalo - Uno, Mayawati; Isa, Ishak; Lukum, Astin (Jurnal Entropi, 2007)
The title of classroom action research is Improving the achievement of concep atom structure thought cooperativeThis research involves the students of class X4 SMA N 3 Gorontalo of in academic year 2008/2009. with cooperative learning model jigasaw type thats have purpose for increasing study result of students class X4 in subject of atom strukture.Based in classroom action prosedure, analysis and reflection on action hypothesis testing doing in a stage. And continuous that is on every ending activities from every cycle. 85 students who on observation paper minimal reach the nice category. The students achievement in cycle I, from 32 students there are 18 students who get more than (6,9), and 14 students get less that (6,9) with the average (6,74), while in the cycle II is improve where 32 students there are 28 students (87,5) get more than 6,9 and students get less than 6,9 with the average 8,0 and the average of applicapibility 82,75. Based on the students achievement in apply of cooperative learning model jigsaw type in structure atom can be improve the students achievement, so the hypothesis in this research is valid.